International investment positions and exchange rate dynamics - Michael Binder; Christian J. Offermanns (Freie Universität Berlin, Fachbereich Wirtschaftswissenschaft, 2014)
We revisit medium- to long-run exchange rate determination, focusing on the role of international investment positions. To do so, we make use of a new econometric framework accounting for conditional long-run homogeneity in heterogeneous dynamic panel data models. In particular, in our model the long-run relationship between effective exchange rates and domestic as well as weighted foreign prices is a homogeneous function of a country's international investment position. We find rather strong support for purchasing power parity in environments of limited negative net foreign asset to GDP positions; furthermore, long-run exchange rate equilibria may have little relation to purchasing power parity outside such environments. We thus argue that the purchasing power parity hypothesis holds conditionally, but not unconditionally, and that international investment positions are an essential component to characterizing this conditionality.
Keywords: F31; F37; C23; 330; exchange rate determination; international financial integration; dynamic panel data models